2016
DOI: 10.1186/s12917-016-0673-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological analysis of bovine ephemeral fever in 2012–2013 in the subtropical islands of Japan

Abstract: BackgroundBovine ephemeral fever (BEF) is a febrile disease of cattle that is transmitted by arthropod vectors such as mosquitoes and Culicoides biting midges. An outbreak of BEF recently occurred in Ishigaki Island and surrounding islands that are located southwest of Japan. In this study, an epidemiological analysis was conducted to understand the temporal and spatial characteristics of the outbreak. Factors associated with the disease spread within Ishigaki Island were investigated by hierarchical Bayesian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 74 publications
(90 reference statements)
0
13
0
2
Order By: Relevance
“…Some reassortment between AINOV and PEAV may occur in nature (Yanase et al ., ), although this phenomenon has not yet been observed by cloning their structure genes (data not shown). In 2012–2013, BEFV broke out in both the Yaeyama Islands, Japan, and Taiwan; BEFV may have been transferred from the Yaeyama Islands to eastern Taiwan through an airstream (Ting et al ., ; Hayama et al ., ). The initial outbreak of BEFV occurred in September 2012 in eastern Taiwan, but the virus soon spread to western Taiwan via Pingtung County; this temporospatial pattern of occurrence is in line with predictions made by airstream simulation (Hayama et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some reassortment between AINOV and PEAV may occur in nature (Yanase et al ., ), although this phenomenon has not yet been observed by cloning their structure genes (data not shown). In 2012–2013, BEFV broke out in both the Yaeyama Islands, Japan, and Taiwan; BEFV may have been transferred from the Yaeyama Islands to eastern Taiwan through an airstream (Ting et al ., ; Hayama et al ., ). The initial outbreak of BEFV occurred in September 2012 in eastern Taiwan, but the virus soon spread to western Taiwan via Pingtung County; this temporospatial pattern of occurrence is in line with predictions made by airstream simulation (Hayama et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In 2012–2013, BEFV broke out in both the Yaeyama Islands, Japan, and Taiwan; BEFV may have been transferred from the Yaeyama Islands to eastern Taiwan through an airstream (Ting et al ., ; Hayama et al ., ). The initial outbreak of BEFV occurred in September 2012 in eastern Taiwan, but the virus soon spread to western Taiwan via Pingtung County; this temporospatial pattern of occurrence is in line with predictions made by airstream simulation (Hayama et al ., ). Another viewpoint indicated that BEFV may spread in a seasonal direction from southern China to southwestern Taiwan (Walker & Klement, ).…”
Section: Discussionmentioning
confidence: 99%
“…Large-and medium-scale outbreaks of BEF repeatedly occurred in Japan until 1989 (18,19). Since then, the epidemics had been limited to the southwestern islands of Japan, which are close to Taiwan (20,21). However, in 2015 a reoccurrence of BEF was reported in the southern end of Kyushu, which is one of the main islands of Japan (22).…”
Section: History Of Endemic and Emerging Arboviruses Affecting Domestmentioning
confidence: 99%
“…As a pioneering study, a backward-trajectory analysis of the BEF epidemic in 2012 in Japan's southwestern islands showed that the estimated potential sources of infected vectors were Southeast Asian countries such as Vietnam and Philippine (21).…”
Section: Research Gaps and Future Directionsmentioning
confidence: 99%
“…It can spread rapidly and lead to considerable economic losses due to decreased-milk production, reduced-male fertility, disruption of stock movement, and even causes death of infected animals [1, 2]. In addition, BEF is believed to be an ancient disease that has been endemic in tropical, subtropical, and temperate regions of Africa, Asia, and Australia [35]. Its causative agent, bovine ephemeral fever virus (BEFV) is an enveloped, nonsegmented, single stranded negative sense RNA virus in the Ephemerovirus genus of the Rhabdoviridae family.…”
Section: Introductionmentioning
confidence: 99%